Revised and extended social commerce technology adoption in e-business of Pakistan - Solangi, Yasir Ali; Solangi, Zulfiqar Ali; Ahmed Maher, Zulfikar; Sheikh Abdul Aziz, Madihah; Hamzah, Mohd Syarqawy; Shah, Asadullah (IIUM Press, 2019)
Social commerce is a new perspective change in modern electronic business procedures bringing together individuals on social media sites and opens up another electronic social marketing channel to establish business. In developing countries like Pakistan, e-business can help organizations using social commerce and social marketing intelligently on particular social network sites to grasp their business clients while they are interacting with their online community on the social media sites. This study investigated consumers’ behavior towards adoption of social commerce and introduced a revised and extended social commerce technology model. The investigation proved the proposed model is valid by confirming loading factor, Kaiser-Mayer-Olkin (KMO), reliability analysis, and structural equation modeling approach for hypotheses tests. The study found Perceived Ease of Use (PEU), Perceived Usefulness (PU), Social Media Influence (SMI), and Risk (RI) have significant impact on social commerce adoption in e-business of Pakistan. More, Trust (TR) and Web experience (WXP) were insignificant that revealed the preventive behavior towards adoption of social commerce in e-business of Pakistan.